Answer:
(x, y) = (4, -2)
Step-by-step explanation:
The coefficient of y in the second equation is double the coefficient of y in the first. We can subtract twice the first equation from the second to eliminate y.
(3x +4) -2(x +2y) = (4) -2(0)
x = 4 . . . . . . . . . simplify
Substituting into the first equation, we have ...
4 +2y = 0
2 +y = 0 . . . . . . divide by 2
y = -2 . . . . . . . . subtract 2
The solution is (x, y) = (4, -2).
Answer:
2 one 0 0 this one
0 0
Step-by-step explanation:
1) 70
2) 110
3) 70
because 110 is equivalent to angle 2. angle 1 and 3 are also equivalent so you add 110 + 110 which equals 220 and subtract 360-220 which equals 140 and divide by 2 to get angles 1 and 3.
Answer: 8n
Let's simplify step-by-step.
(2(n+1)−1)2−(2n−1)2
Distribute:
=4n2+4n+1+−4n2+4n+−1
Combine Like Terms:
=4n2+4n+1+−4n2+4n+−1
=(4n2+−4n2)+(4n+4n)+(1+−1)
=8n